1985
DOI: 10.1128/jb.163.3.1196-1202.1985
|View full text |Cite
|
Sign up to set email alerts
|

Identification of livG, a membrane-associated component of the branched-chain amino acid transport in Escherichia coli

Abstract: Branched-chain amino acids are transported into Escherichia coli by two osmotic shock-sensitive systems (leucine-isoleucine-valine and leucine-specific transport systems). These high-affinity systems consist of separate periplasmic binding protein components and at least three common membrane-bound components. In this study, one of the membrane-bound components, livG, was identified. A toxic analog of leucine, azaleucine, was used to isolate a large number of azaleucine-resistant mutants which were defective i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 27 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…If their effect were exerted through changes in membrane structure then it would not be stereo-specific and other hydrophobic amino acids, like Ile, Phe and Trp would have a similar effect. The same reasoning partially applies for changes in membrane potential or any other possible effect caused by the active transport of the amino acids; although stereo-specificity could arise from the transport system(s), other amino acids would be expected to have an inhibitory effect, especially Ile, which shares the same pathway of active transport with Val (Nazos et al, 1985).…”
Section: Leucine Exerts Its Effect Through the Tar Moiety Of Tazmentioning
confidence: 96%
“…If their effect were exerted through changes in membrane structure then it would not be stereo-specific and other hydrophobic amino acids, like Ile, Phe and Trp would have a similar effect. The same reasoning partially applies for changes in membrane potential or any other possible effect caused by the active transport of the amino acids; although stereo-specificity could arise from the transport system(s), other amino acids would be expected to have an inhibitory effect, especially Ile, which shares the same pathway of active transport with Val (Nazos et al, 1985).…”
Section: Leucine Exerts Its Effect Through the Tar Moiety Of Tazmentioning
confidence: 96%
“…Mutations in the livF and livH genes did not show a reduced colonization potential, but displayed an impaired induction of systemic resistance. In E. coli, LivF and LivH are associated with the ABC transport system for branched-chain amino acids (Nazos et al, 1985). Based on sequence similarities, LivH is the membrane component and LivF is the ATP-binding component of the ABC transport complexes (Adams et al, 1990).…”
Section: Discussionmentioning
confidence: 94%
“…Quite recently, we found that the LIV‐I/LS system [22–27], initially assumed to be a branched‐chain amino acid‐specific transporter, is the third phenylalanine transporter and has a broader substrate specificity than previously reported [28]. This finding led us to envisage the possible linkage between the alleviating effects of phenylalanine and branched‐chain amino acids on azaserine toxicity, and prompted us to examine whether or not the LIV‐I/LS system is involved in the azaserine sensitivity of E. coli .…”
Section: Introductionmentioning
confidence: 94%